Metabolic syndrome in Thai adolescents and associated factors: the Thai National Health Examination Survey V (NHES V) - Sirinapa Siwarom; Wichai Aekplakorn; Kwanchai Pirojsakul; Witchuri Paksi; Pattapong Kessomboon; Nareemarn Neelapaichit; Suwat Chariyalertsak; Sawitri Assanangkornchai; Surasak Taneepanichskul (BMC, 2021)
Abstract Background Presence of metabolic syndrome (MetS) in early life may influence cardiovascular outcome later in adulthood. There is limited data regarding MetS among Thai adolescents. This study aimed to estimate the prevalence of MetS and related factors in Thai adolescents. Methods Data on MetS components of 1934 Thai adolescents aged 10-16 years were obtained from the 5th National Health Examination Survey. Age at first screen time exposure, duration of screen time, frequency of food intake and physical activities were collected from interviews. MetS was defined according to 3 definitions: International Diabetes Federation (IDF), Cook's, and de Ferranti's. Results The prevalence of MetS was 4.1% by IDF, 8.0% by Cook's, and 16.8% by de Ferranti's definition. The overall prevalence was higher in male (19.0%) than female adolescents (15.3%). The most common MetS components composition among Thai adolescents was high waist circumference with high serum triglyceride and low HDL-cholesterol (40.0% for IDF, 22.6% for Cook's and 43.5% for de Ferranti's definition). Exposure to screen media during the first 2 years of life had a 1.3- fold increased odds of MetS by 1 out of 3 definitions (OR 1.30, 95% CI. 1.01-1.68). Duration of physical activity associated with decreased odds of MetS by Cook's definition (OR 0.96, 95% CI. 0.92-0.99). Conclusions The prevalence of MetS among Thai adolescents was higher than previously reported by other studies. Screen media exposure during the first 2 years of life should be discouraged and measures to promote physical activity among children and adolescents should be strengthen.